ANALYSIS OF MATHEMATICS MID TEST QUESTIONS FOR CLASS VII SMP EDUCATION 21 KULIM - Putri, Anisa; Roza, Yenita; Maimunah, Maimunah (Jurnal Pendidikan Matematika dan IPA, 2022)
This study aims to analyze the items for the mathematics middle exam at SMP Education 21 Kulim grade VII for the 2020/2021 academic year in terms of the level of validity, reliability, level of difficulty, and discriminating power of questions. The research method used is descriptive quantitative. The data is in the form of 20 essay questions which are analyzed using Anates software Version 4.0. The results of the analysis of the level of validity are stated to be not good because overall it has a valid percentage of 70%. From the level of reliability, it is stated that it is not good because it has a reliability of 0.7. From the level, it is stated that the difficulty level is not good because 70% of the total number is classified as moderate. From the power of distinction, it is stated that the overall question has good distinguishing power because 70% of the total questions are classified as good. The solution is that these questions are not used and revisions are made. Thus, based on the test quality indicators, it can be said that the final semester tests are not of high quality.